Fournier’s gangrene in a female patient: a case report: Fournierjeva gangrena pri ženski: prikaz primera - Novak Skodič, Nadja; Magdalenič, Tomislav; Petrun, Gregor; Hebar, Timea; Takač, Iztok (Acta Medico-Biotechnica, 2026)
Purpose: Fournier’s gangrene is a rare life-threatening form of necrotizing fasciitis that affects the genital, perineal and perianal regions. A significantly higher mortality rate occurs in females due to anatomic differences and greater susceptibility to peritonitis and retroperitonitis. Common risk factors for Fournier’s gangrene include diabetes melitus, substance abuse, liver failure, and immunosuppression. Case presentation: A 73-year-old woman collapsed and was transported to the emergency room tachycardic and in atrial fibrillation. Earlier that day she had an appointment with her gynecologist for evaluation of an inflamed, erythematous, painful left labia, which the gynecologist treated with antibiotics.